“THEY HAVE OPENED OUR MOUTHS”: INCREASING WOMEN’S SKILLS AND MOTIVATION FOR SEXUAL COMMUNICATION WITH YOUNG PEOPLE IN RURAL SOUTH AFRICA - Phetla, Godfrey (2008)
Communication between parents and young people about sex has been identified as a positive influence on young people’s sexual behavior. This article presents findings from South Africa, where a social intervention to reduce levels of HIV and intimate partner violence actively promoted sexual communication between adults and young people. We assessed this component of the program using quantitative and qualitative methods, collecting data through surveys, direct observation, interviews, and focus group discussions. Women participating in intervention activities reported sexual communication with children significantly more often than matched women in the control group (80.3% vs. 49.4%, adjusted risk ratio 1.59 (1.31-1.93). The content of communication with young people also appears to have shifted from vague admonitions about the dangers of sex to concrete messages about reducing risks. The congruence between these findings and existing literature on parent-child sexual communication suggests that conceptual frameworks and programs from developed settings can be adapted effectively for resource-poor contexts.